2010
DOI: 10.1093/tropej/fmq102
|View full text |Cite
|
Sign up to set email alerts
|

Measles-Mumps-Rubella Revaccination; 18 Months vs. 4-6 Years of Age: Potential Impacts of Schedule Changes

Abstract: This study showed that the majority of younger children were susceptible to MMR infection before revaccination. Earlier age policy provides more protection against MMR in preschool-aged children. Rubella strain seems to be less potent than reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, vaccinerelated factors such as lack of adequate potency of vaccine because of using more thermo-labile strains, inadequate control of cold chain shipment, storage, use, and other probable factors may be responsible [45][46][47]. Our assumption regarding the inadequate potency of vaccine is based on the results of studies that were designed to investigate the immunogenicity of MMR vaccine currently used in Iran [48][49][50][51][52][53]. The majority of these studies showed lower rates of seroconversion following the first and/or the second doses of MMR vaccine after the age of 12 months (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vaccine-related factors such as lack of adequate potency of vaccine because of using more thermolabile strains, inadequate control of cold chain shipment/storage/ and use, and other probable factors may be responsible (45)(46)(47) . Our assumption regarding the inadequate potency of vaccine is based on the results of studies that were designed to investigate the immunogenicity of MMR vaccine currently in used in Iran (48)(49)(50)(51)(52)(53) . The majority of these studies showed lower rates of seroconversion following the rst and/or the second doses of MMR vaccine after the age of 12 months ( Table 5).…”
Section: Discussionmentioning
confidence: 99%